Large-scale opacification of a hydrophilic/hydrophobic intraocular lens. Issue 2 (March 2020) - Costa, José F; Bompastor-Ramos, Paula; Marques, Marco; Henriques, Jorge; Póvoa, João; Lobo, Conceição; Alió, Jorge L; Werner, Liliana; Murta, Joaquim
Purpose: To determine the prevalence and risk factors related to the opacification of the LS-502-1 intraocular lens. Methods: Cross-sectional study including patients submitted to cataract surgery between January 2010 and March 2012, with implantation of the LS-502-1 intraocular lens. Past medical history was registered and a complete ophthalmologic evaluation, that included best-corrected visual acuity, slit-lamp examination and fundoscopy, was performed. Anterior segment photographs were taken whenever intraocular lens opacification was present. Results: One hundred and sixty-nine eyes of 154 patients were included, mean age 78.5 ± 7.9 years. The average follow-up after intraocular lens implantation was 65.6 ± 10.0 months. Intraocular lens opacification was seen in 53.3% (n = 90) and presented as one of four different patterns: peripheral (15.6%, n = 14), central (4.4%, n = 4), diffuse (71.1%, n = 64) and superficial white deposits (8.9%, n = 8). There was no statistically significant association with systemic or ophthalmic conditions. In patients with bilateral implantation, intraocular lens opacification in one eye was significantly related to intraocular lens opacification in the fellow eye. A significant variability in opacification was found across intraocular lens serial numbers: the odds ratio for opacification in intraocular lens with serial number beginning with 200003 was 6.0 when comparing with the remaining lenses. Conclusion: The opacification prevalence of the LS-502-1 intraocular lens was 53.3%, which is the highest ever described for any intraocular lens model. Our results suggest that this occurrence is secondary to an interaction between unknown patient variables and problems related to intraocular lens manufacturing and storage procedures.